IBN SINA (AVICENA): o intelecto e a cura da alma - Filho, Miguel Attie (2007)
This article presents a translation of the prologue of the work “Al-Sifa’” written by Ibn Sina (980-1037.C.) and argues elements on the question of the soul and the intellect. KEY WORDS – Ibn Sina. Avicenna. Arabic Philosophy. Soul. Intellect.